A filling injection containing porous hydroxyapatite and sodium hyaluronate

By using a combination injection of porous hydroxyapatite and sodium hyaluronate, the problems of low spherical morphology and migration after injection were solved, and the dual goals of dermal filling effect and safety were achieved.

CN118634361BActive Publication Date: 2025-04-08BEIJING ZHONGTIAN CHANGHE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410672471.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-28
Publication Date
2025-04-08
Estimated Expiration
2044-05-28

AI Technical Summary

Technical Problem

In the prior art, the spherical shape of hydroxyapatite is not high, resulting in poor skin filling effect; the dispersion of hydroxyapatite in the matrix is ​​easy to block the needle; hydroxyapatite is prone to migration after injection, resulting in skin collapse.

Method used

Using a combination of porous hydroxyapatite and sodium hyaluronate injection, by controlling the particle size, sphericality and porosity of porous hydroxyapatite, combined with the degradation characteristics of sodium hyaluronate, fillers with appropriate disintegration time and degradation time were prepared.

Benefits of technology

It achieves a full and natural skin filling effect, while avoiding safety hazards caused by the degradation time of hydroxyapatite, and meeting the filling effect and safety requirements of the medical beauty field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118634361B_ABST
    Figure CN118634361B_ABST
Patent Text Reader

Abstract

The present invention provides a filling injection containing porous hydroxyapatite and sodium hyaluronate, comprising the following raw materials in parts by mass: 10-16 parts of porous hydroxyapatite, 2-4 parts of sodium hyaluronate, 0.8-1.5 parts of cross-linked sodium hyaluronate, 0.5-1 parts of growth factor, 100-150 parts of aqueous solution for injection; the particle size is 20-60 μm, the sphericity is above 85%, and the porosity is 30-45%. The present invention makes hydroxyapatite with a specific morphology by itself, which has good skin support performance; at the same time, it has very satisfactory degradation performance, can have a good support effect on the skin within the validity period, and will not excessively prolong the degradation time, while satisfying the skin beauty effect and safety of the skin filling injection in the field of medical beauty.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of injections for medical aesthetic skin filling, and in particular to an injection for filling containing porous hydroxyapatite and sodium hyaluronate. Background Art

[0002] Hydroxyapatite has good biocompatibility and biodegradability, and was previously widely used in the field of bone repair. In recent years, due to the advancement of nanomaterial synthesis technology, hydroxyapatite has begun to be used as an injectable cosmetic facial filler. The main requirements for hydroxyapatite in injections for medical skin filling are controllable particle size and high sphericity. Otherwise, it is difficult to achieve safe and good skin filling effects. Sodium hyaluronate is non-immunogenic and has good biosafety, and is a common gel matrix for skin filling in the medical field. There are many reports on the combined use of hydroxyapatite and sodium hyaluronate in the prior art. However, there are some problems, such as the low sphericity of hydroxyapatite, which has a poor skin filling effect; the dispersion problem of hydroxyapatite in the matrix, which is easy to clog the needle; hydroxyapatite is prone to migration after injection, leading to skin collapse and other problems. For example, the hydroxyapatite-containing injection filler reported in CN110292655A includes the following components by weight: 20-80 parts of hydroxyapatite, 1-20 parts of gel matrix, 1-20 parts of osmotic pressure regulator, and 100 parts of buffered saline solution. The patent uses a mixture of sodium carboxymethylcellulose, hydroxypropyl cellulose, carbomer and triethanolamine as a gel matrix to obtain a gel with high elastic modulus and dynamic viscosity. The patent is to improve the durability by extending the retention time of hydroxyapatite in the body. Hydroxyapatite is used in skin filling injection microspheres. The main problem is that the time when hydroxyapatite starts to disintegrate and loses the filling effect is short. If the disintegration time of hydroxyapatite is simply extended, its degradation time will be correspondingly extended, and long-term retention in the human body also has safety issues. Therefore, it is necessary to develop a kind of effective skin support time of 2-3 months, and the degradation time is within 4 months, and the disintegration time (sphericity loss, unable to effectively support the skin) and degradation time (time of complete loss of sphericity) are relatively small. This can meet the requirements of effective skin filling and injection safety at the same time.

[0003] CN115040689A discloses a high-fluidity hydroxyapatite nanomaterial and a preparation method thereof. The invention comprises the following steps: calcium chloride is used as a calcium source, disodium hydrogen phosphate is used as a phosphorus source, cyclohexane hexacarboxylic acid and pretreated carbon microspheres are used as templates, the pretreated carbon microspheres are removed at high temperature to obtain hollow hydroxyapatite; a mixed solution of KH-550, anhydrous ethanol and deionized water is added to the hollow hydroxyapatite, the pH value is adjusted to 10 by sodium hydroxide, the mixture is reacted at 60-70°C for 7-8h, the mixture is centrifuged and washed, and vacuum dried to obtain material A; material A is dissolved in xylene, ultrasonically dispersed for 20-30min, stannous octoate is added, the mixture is reacted for 2-3h in a nitrogen environment, the reaction time is 130-140°C, a xylene solution of lactide is added, the reaction is continued for 18-20h, the mixture is centrifuged and washed, and vacuum dried to obtain grafted hydroxyapatite; the grafted hydroxyapatite is taken, placed in a solution containing a growth factor and soaked for 20-30min, and taken out to obtain a hydroxyapatite nanomaterial loaded with the growth factor. In order to increase the loading capacity of hydroxyapatite for growth factors, this patent adopts a method of preparing hollow hydroxyapatite and grafting. The preparation method is complicated, and carbon spheres are used as templates. Although hollow hydroxyapatite with high sphericity can be obtained, the residual carbon content is high and the safety is reduced.

[0004] The inventors found that in the past, in order to pursue high sphericity, hydroxyapatite was generally prepared into a solid sphere, but the degradation time would be greatly prolonged, and there would be safety hazards if it was retained in the skin for a long time. At present, there is a technology for supporting porous microspheres with hydroxyapatite, but the elastic modulus of porous microspheres is poor, and the support is not good, which makes it difficult to be used for skin injection. In addition, the current general use of polymers as pore-forming agents will result in carbon residues in the product, which also poses a safety hazard. Summary of the invention

[0005] In order to solve the defects of the injection containing hydroxyapatite porous microspheres in the prior art, such as the small difference between the degradation time and the disintegration time, the inability to meet the filling effect and safety requirements at the same time, and the problem of carbon residue caused by the polymer pore former, the present invention provides the following technical solutions:

[0006] A filling injection containing porous hydroxyapatite and sodium hyaluronate comprises the following raw materials in parts by mass: 10-16 parts of porous hydroxyapatite, 2-4 parts of sodium hyaluronate, 0.8-1.5 parts of cross-linked sodium hyaluronate, 0.5-1 part of growth factor, and 100-150 parts of aqueous solution for injection; the particle size is 20-60 μm, the sphericity is above 85%, and the porosity is 30-45%.

[0007] Furthermore, the porous hydroxyapatite has a particle size of 30-50 μm, a sphericity of more than 90%, and a porosity of 35-40%.

[0008] Furthermore, the molecular weight of the sodium hyaluronate is 300,000-500,000, and the molecular weight of the cross-linked sodium hyaluronate is 800,000-2,000,000.

[0009] The porous hydroxyapatite of the present invention has a suitable surface micromorphology, which can play a good role in supporting the skin; it has a suitable porosity and can load beneficial ingredients such as growth factors. More importantly, the surface of the prepared porous hydroxyapatite is similar to the cerebral cortex hook, and has a large number of rich pore structures, good support, high elastic modulus, and is used as a filler for medical skin injection, lubricating the wrinkles of the skin, and making the skin filling effect full and natural. More importantly, the porous hydroxyapatite of the present invention has a suitable disintegration time and degradation time, and the difference between the two is short, which avoids the problem of long degradation time and easy migration of solid microspheres, and also avoids the defect of poor filling effect caused by insufficient support and poor sphericity of porous microspheres. More importantly, the porous hydroxyapatite of the present invention directly interacts with the fibroblasts of the dermis, and the direct mechanical conduction weakens the immune system, while promoting collagen regeneration, it has a lower inflammatory response. In addition, the present invention adopts sodium hyaluronate and cross-linked hyaluronic acid compound, each of which plays a role and can also synergistically improve the filling effect, so that the excellent filling effect is further extended. Sodium hyaluronate has a short degradation time, while cross-linked sodium hyaluronate has a long degradation time. The combination of the two can ensure that the filling injection of the present invention can maintain a good filling effect within a validity period of 3-6 months while having high safety.

[0010] Furthermore, the method for preparing the porous hydroxyapatite comprises the following steps:

[0011] Polyoxyethylene nonylphenol phosphate as an organic phosphorus source is dissolved in an organic solvent miscible with water to obtain solution A, and an inorganic phosphorus source is dissolved in water to obtain solution B. After solution A and solution B are evenly mixed, an aqueous solution of a calcium source is added, the pH is adjusted to 4-6, a polymer pore-forming agent is added, and the mixture is evenly stirred and heated to 100-130°C and stirred continuously for a hydrothermal reaction for 6-10 hours. After cooling, the mixture is allowed to stand for aging for 3-5 hours, and the obtained precipitate is washed and calcined to obtain porous hydroxyapatite. The amounts of solution A and solution B are such that the molar ratio of P in the organic phosphorus source to P in the inorganic phosphorus source is 2-3:7-10. The amounts of the phosphorus source (the sum of the organic phosphorus source and the inorganic phosphorus source) and the calcium source are such that the molar ratio of P:Ca in the system is 1.6-1.8:1.

[0012] The present invention selects polyoxyethylene nonylphenol phosphate as an organic phosphorus source, which has the functions of both a phosphorus source and a surfactant, does not need to add other surfactants, and does not introduce new impurities. In addition, the inventors have found that among many organic phosphorus sources, only the porous hydroxyapatite prepared by polyoxyethylene nonylphenol phosphate has a specific morphology. It may be that the hydrolysis rate and the inorganic phosphorus source have a coordinated effect, and the synergistic cooperation can prepare porous hydroxyapatite with a suitable microscopic morphology.

[0013] Furthermore, the organic solvent miscible with water is selected from at least one of ethanol, glycerol, tetrahydrofuran, acetone, dimethyl ether, and mannitol; in solution A, the molar concentration of the organic phosphorus source in terms of P is 0.2-0.3 mol / L; the inorganic phosphorus source is selected from at least one of disodium hydrogen phosphate, sodium dihydrogen phosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate; in solution B, the molar concentration of the inorganic phosphorus source in terms of P is 0.5-1 mol / L; the calcium source is selected from at least one of calcium chloride and calcium nitrate.

[0014] The inventors found that the type of phosphorus source directly affects the sphericity and surface morphology of porous hydroxyapatite. The phosphorus source of the present invention adopts a compound of an organic phosphorus source and an inorganic phosphorus source. The inorganic phosphorus source is the main source of P and has a fast hydrolysis rate; the organic phosphorus source plays the role of a phosphorus source, a surfactant, and a pore modifier at the same time. The two work synergistically to prepare porous hydroxyapatite with excellent performance, high sphericity, and suitable microscopic morphology. It has a suitable degradation time and a long disintegration time, and the gap between the disintegration time and the degradation time is reduced, while satisfying both cosmetic effects and safety.

[0015] Furthermore, the amount of phosphorus source (the sum of organic phosphorus source and inorganic phosphorus source) and calcium source is such that the molar ratio of P:Ca in the system is 1.65-1.7:1.

[0016] Furthermore, the polymer pore former is selected from at least one of polyvinyl alcohol, hydroxypropyl methylcellulose, chitosan, polydextrose, polyethylene, polypropylene, and polycarbonate, preferably polyvinyl alcohol. The ratio of the polymer pore former to Ca in the calcium source is 20-30 g: 1 mol.

[0017] In a preferred technical solution of the present invention, the polymer pore-forming agent is a compound of low molecular weight polyvinyl alcohol and high molecular weight polyvinyl alcohol, the number average molecular weight of the low molecular weight polyvinyl alcohol is 5000-8000 g / mol, and the number average molecular weight of the high molecular weight polyvinyl alcohol is 20000-30000 g / mol. More preferably, the mass ratio of low molecular weight polyvinyl alcohol to high molecular weight polyvinyl alcohol is 4-7:1. The inventor unexpectedly found that the porous hydroxyapatite prepared by the compound of low molecular weight and high molecular weight polyvinyl alcohol has a more suitable pore structure, which not only has a better support effect on the skin, but also has a larger growth factor loading capacity.

[0018] Furthermore, washing is performed by washing with water until the pH of the supernatant is 7-7.5, and then washing with ethanol; the calcination is performed in an oxygen-containing atmosphere (such as air, oxygen), above 320°C, such as 320-360°C for 6-10h. The present invention does not use a pore-forming agent that requires high-temperature calcination treatment, and polyvinyl alcohol can be smoothly calcined and completely removed at above 320°C, without any carbon residue, and can be safely used as a filler for skin injection. In the past, materials such as carbon balls were used as pore-forming agents / templates to prepare porous hollow hydroxyapatite microspheres, which required high temperatures to remove the pore-forming agents, and were difficult to remove completely, with a small amount of carbon residue, which posed certain safety risks for skin filling injections.

[0019] Furthermore, the aqueous solution for injection is physiological saline or a phosphate buffer solution with a pH of 6.8-7.2; the osmotic pressure regulator is used to adjust the osmotic pressure of the injection to 290-330mOsmol / kg, and the osmotic pressure regulator includes but is not limited to at least one of glycerol, mannitol, and sorbitol.

[0020] Furthermore, the growth factor is selected from at least one of fibroblast growth factor, epidermal growth factor, and keratinocyte growth factor. The porous hydroxyapatite used in the present invention can not only achieve a large loading amount of growth factor, but more importantly, after the porous hydroxyapatite is loaded with growth factor, it can protect the growth factor from being phagocytosed by macrophages after injection, thus avoiding the defect that the growth factor cannot reach the dermis of the skin to play a role.

[0021] Furthermore, the filling injection also includes other excipients, such as at least one selected from analgesics, vitamins, antibacterial agents, and antioxidants; examples of the analgesics include but are not limited to lidocaine; examples of the vitamins include but are not limited to vitamin C, vitamin D, vitamins, vitamin B6, and vitamin B7; examples of the antibacterial agents include but are not limited to benzalkonium bromide.

[0022] The present invention also provides a method for preparing the above-mentioned filling injection containing porous hydroxyapatite and sodium hyaluronate, comprising the following steps: uniformly mixing the porous hydroxyapatite with growth factors and water for injection to achieve sufficient loading of the porous hydroxyapatite with the growth factors, and then adding sodium hyaluronate and cross-linked sodium hyaluronate, and optionally, adding auxiliary materials, mixing uniformly, and sterilizing to obtain the filling injection containing porous hydroxyapatite and sodium hyaluronate.

[0023] Furthermore, the sterilization is carried out by γ-ray irradiation.

[0024] Compared with the prior art, the present invention has the following technical advantages:

[0025] 1. The present invention makes self-made hydroxyapatite with a specific morphology, which has a surface morphology similar to the gyrus of the cerebral cortex and a rich porous structure, and has good skin support performance; at the same time, it has very satisfactory degradation performance, which can provide good support for the skin within the validity period, and at the same time will not excessively prolong the degradation time, while meeting the skin beauty effect and safety of skin filler injections in the field of medical beauty.

[0026] 2. The present invention uses low molecular weight and high molecular weight polyvinyl alcohol, which work together to make the porous hydroxyapatite more suitable for skin injection, with a more developed pore structure, which is conducive to the loading of growth factors and can avoid the risk of growth factors being phagocytosed by macrophages, so that the growth factors can be delivered to the desired target site more effectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the SEM image of the porous hydroxyapatite prepared in Preparation Example 1.

[0028] Figure 2 This is the SEM image of the porous hydroxyapatite prepared in Preparation Example 2.

[0029] Figure 3 This is a SEM image of the porous hydroxyapatite prepared in Comparative Preparation Example 1.

[0030] Figure 4 This is the SEM image of the porous hydroxyapatite prepared in Comparative Preparation Example 2.

[0031] Figure 5 This is the SEM image of the porous hydroxyapatite prepared in Comparative Preparation Example 3.

[0032] Figure 6 This is a pathological picture of the injection of Example 1 implanted in the subcutaneous tissue of the back of a rabbit for 4 weeks. DETAILED DESCRIPTION

[0033] To make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be described in detail below. The following examples are convenient for better understanding of the present invention, but are not intended to limit the present invention. The experimental methods in the following examples are conventional methods unless otherwise specified.

[0034] Unless otherwise specified, the “parts” in the embodiments of the present invention are parts by mass, and the “%” are percentages by mass.

[0035] Preparation Example 1

[0036] Dissolve polyoxyethylene nonylphenol phosphate in ethanol solution A at a concentration of 0.2 mol / L, dissolve disodium hydrogen phosphate in water to obtain solution B at a concentration of 1 mol / L, mix 100 mL of solution A and 100 mL of solution B evenly, and add CaCl 2 The aqueous solution has a concentration of 0.5 mol / L, CaCl 2 The amount of solution used makes the P:Ca ratio in the system 1.68, the pH is adjusted to 4.5, polyvinyl alcohol (a compound of polyvinyl alcohol with a number average molecular weight of 5000g / mol and polyvinyl alcohol with a number average molecular weight of 20000g / mol) is added, the amount of polyvinyl alcohol is such that the ratio of the mass of polyvinyl alcohol to the Ca of the calcium source is 20g:1mol, after stirring evenly, the temperature is raised to 120°C and stirring is continued for hydrothermal reaction for 10 hours, after cooling, it is allowed to stand and age for 5 hours, the obtained precipitate is first washed with water until the pH of the supernatant is 7, then washed with anhydrous ethanol, dried in a vacuum oven at 60°C for 10 hours, the material is transferred to a muffle furnace, the temperature is raised to 350°C in an air atmosphere, and calcined for 10 hours to obtain porous hydroxyapatite.

[0037] Preparation Example 2

[0038] The other conditions were the same as those in Example 1, except that 150 mL of solution A and 70 mL of solution B were mixed evenly.

[0039] Preparation Example 3

[0040] The other conditions are the same as those in Example 1, except that the polyvinyl alcohols are all polyvinyl alcohols with a number average molecular weight of 5000 g / mol.

[0041] Preparation Example 4

[0042] The other conditions are the same as those in Example 1, except that the polyvinyl alcohols are all polyvinyl alcohols with a number average molecular weight of 20,000 g / mol.

[0043] Comparative Preparation Example 1

[0044] Other conditions were the same as those in Example 1, except that no organic phosphorus source was added, and the phosphorus source was all inorganic phosphorus source disodium hydrogen phosphate, keeping the system Ca:P unchanged.

[0045] Comparative Preparation Example 2

[0046] The other conditions were the same as those in Example 1, except that the organic phosphorus source was replaced with disodium hydroxyethylene diphosphate, and the Ca:P ratio of the system was kept unchanged.

[0047] Comparative Preparation Example 3

[0048] Other conditions were the same as those in Example 1, except that the amount of polyvinyl alcohol used satisfied the ratio of the mass of polyvinyl alcohol to the Ca of the calcium source of 10 g:1 mol.

[0049] Figure 1 is a SEM image of the porous hydroxyapatite prepared in Preparation Example 1; Figure 2 is a SEM image of the porous hydroxyapatite prepared in Preparation Example 2; Figure 3 is a SEM image of the porous hydroxyapatite prepared in Comparative Preparation Example 1; Figure 4 This is a SEM image of the porous hydroxyapatite prepared in comparative preparation example 2. The above shows that only by adding a specific organic phosphorus source polyoxyethylene nonylphenol phosphate can a porous hydroxyapatite with a surface similar to the cerebral cortex and a rich pore structure be prepared. Figure 5 : is a SEM picture of the porous hydroxyapatite prepared in comparative preparation example 3. It can be seen that the amount of the pore-forming agent cannot be too small, otherwise the porous hydroxyapatite with sufficient porosity and rich pore structure cannot be obtained.

[0050] Effect Example 1

[0051] The hydroxyapatite obtained in the above preparation examples and comparative preparation examples was subjected to the following performance tests:

[0052] 1. Sphericity It was tested using a scanning electron microscope and calculated using image processing software.

[0053] 2. Cytotoxicity The test was conducted using GB / T 16886.5-2017.

[0054] 3. Carbon residue Tested with XPS spectrum.

[0055] 4. Stability test The prepared porous hydroxyapatite is prepared into a 5wt% aqueous solution with physiological saline, and stored at 25±2°C for 60 days to observe whether there is agglomeration. If a uniform and stable single phase is maintained, it passes the stability test, and if there is visible phase separation or precipitation, it fails the stability test.

[0056] 5. Disintegration time and Degradation timeThe porous hydroxyapatite was prepared into a 1wt% aqueous solution with a PBS buffer solution of pH 7.3, and tested at a constant temperature of 37°C. The disintegration time is the time when the sphericity is less than 70%, at which time the hydroxyapatite microspheres can no longer support the skin; the degradation time is the time when the sphericity of the hydroxyapatite microspheres is completely disintegrated. The results are shown in Table 1.

[0057] Table 1 Porous hydroxyapatite test

[0058]

[0059] Effect Example 2

[0060] 10g of the porous hydroxyapatite prepared in the above preparation examples and comparative preparation examples was immersed in 100mL of 0.5g / L growth factor aqueous solution, and taken out after immersion for 5 hours. The concentration of the growth factor aqueous solution after immersion was tested by ultraviolet spectrophotometry, and the loading amount of the porous hydroxyapatite for fibroblast growth factor was calculated. The results are shown in Table 2 below.

[0061] Table 2 Fibroblast Growth Factor Loading Test

[0062]

[0063] Example 1

[0064] 15 parts of porous hydroxyapatite prepared in Preparation Example 1, 0.2 parts of fibroblast growth factor, 0.3 parts of epidermal growth factor, and 100 parts of 0.9% normal saline are mixed evenly to achieve sufficient loading of the porous hydroxyapatite with the growth factors. Then, 3 parts of sodium hyaluronate (molecular weight 300,000) and 1 part of cross-linked sodium hyaluronate (molecular weight 1.5 million) and 0.3 parts of lidocaine are added and mixed evenly. The osmotic pressure is adjusted to 300mOsmol / kg with mannitol, and γ irradiation is performed for sterilization to obtain a filling injection containing porous hydroxyapatite and sodium hyaluronate.

[0065] Example 2

[0066] The other conditions are the same as those in Example 1, except that the porous hydroxyapatite is replaced by the porous hydroxyapatite prepared in Preparation Example 2 of equal mass.

[0067] Example 3

[0068] The other conditions are the same as those in Example 1, except that the porous hydroxyapatite is replaced by the porous hydroxyapatite prepared in Preparation Example 3 of equal mass.

[0069] Example 4

[0070] The other conditions are the same as those in Example 1, except that the porous hydroxyapatite is replaced by the porous hydroxyapatite prepared in Preparation Example 4 of equal mass.

[0071] Comparative Example 1

[0072] The other conditions are the same as those in Example 1, except that the porous hydroxyapatite is replaced by the porous hydroxyapatite prepared in Comparative Preparation Example 1 of equal mass.

[0073] Comparative Example 2

[0074] The other conditions are the same as those in Example 1, except that the porous hydroxyapatite is replaced by the porous hydroxyapatite prepared in Comparative Preparation Example 2 of equal mass.

[0075] Comparative Example 3

[0076] The other conditions are the same as those in Example 1, except that the porous hydroxyapatite is replaced by the porous hydroxyapatite prepared in Preparation Example 5 of equal mass.

[0077] Effect Example 3

[0078] The injections prepared in the above examples and comparative examples were subjected to the following tests, and the results are shown in Table 3.

[0079] Table 3 Injection effect test

[0080]

[0081] Effect Example 4

[0082] Male Wistar rats were randomly divided into 8 groups, 10 in each group, and the injection was injected into the same area on the back of all rats. The control group was injected with 5 mL of normal saline, and the other groups were injected with 5 mL of the injection of Examples 1-4 and Comparative Examples 1-3, respectively. After injection, the rats were fed a normal diet, and the injection site was observed after 3d, 5d, and 10d, and the effectiveness was evaluated according to the firmness of the injection area. The results are shown in Table 4 below.

[0083] Table 4 Rat injection evaluation

[0084]

[0085] Effect Example 5

[0086] 0.5 ml of the injection of Example 1 was implanted into the subcutaneous tissue of the rabbit's back, and the effects of the sample on the surrounding tissue, collagen growth, and material degradation were observed 4, 8, 12, and 52 weeks after implantation. Histological evaluation was performed according to the semi-quantitative scoring system of GB / T16886.6-2022 standard.

[0087] Figure 6This is a pathological picture of the injection of Example 1 implanted in the subcutaneous tissue of the back of a rabbit for 4 weeks. It can be seen that after 4 weeks of implantation, the implantation point has a capsule wall formed by medium-thick mature collagen fibers, round materials can be seen in the cavity, new blood vessels are abundant, a few lymphocytes, occasional multinuclear leukocytes, macrophages and multinuclear giant cells can be seen. The average score is 8.46, indicating that the inflammatory reaction is small.

Claims

1. A filling injection containing porous hydroxyapatite and sodium hyaluronate, characterized in that: The invention comprises the following raw materials in parts by weight: 10-16 parts of porous hydroxyapatite, 2-4 parts of sodium hyaluronate, 0.8-1.5 parts of cross-linked sodium hyaluronate, 0.5-1 parts of growth factor, and 100-150 parts of aqueous solution for injection; the porous hydroxyapatite has a particle size of 20-60 μm, a sphericity of more than 85%, and a porosity of 30-45%; The preparation method of porous hydroxyapatite comprises the following steps: dissolving polyoxyethylene nonylphenol phosphate as an organic phosphorus source in an organic solvent miscible with water to obtain solution A, dissolving an inorganic phosphorus source in water to obtain solution B, mixing solution A and solution B evenly, adding an aqueous solution of a calcium source, adjusting the pH to 4-6, adding a polymer pore-forming agent, stirring evenly, heating to 100-130°C, continuing stirring to carry out a hydrothermal reaction for 6-10 hours, cooling and standing for aging for 3-5 hours, washing the obtained precipitate, and calcining to obtain porous hydroxyapatite; the amounts of solution A and solution B satisfy that the molar ratio of P in the organic phosphorus source to P in the inorganic phosphorus source is 2-3:7-10; the amounts of the phosphorus source and the calcium source make the molar ratio of P:Ca in the system be 1.6-1.8:1; and the phosphorus source is the sum of the organic phosphorus source and the inorganic phosphorus source.

2. The filling injection according to claim 1, characterized in that: The porous hydroxyapatite has a particle size of 30-50 μm, a sphericity of more than 90%, and a porosity of 35-40%.

3. The injection for filling according to claim 1, characterized in that: The molecular weight of the sodium hyaluronate is 300,000-500,000, and the molecular weight of the cross-linked sodium hyaluronate is 800,000-2,000,000.

4. The filling injection according to claim 1, characterized in that: In the preparation method of porous hydroxyapatite, the organic solvent miscible with water is selected from at least one of ethanol, glycerol, tetrahydrofuran, acetone, dimethyl ether and mannitol; in solution A, the molar concentration of the organic phosphorus source in terms of P is 0.2-0.3 mol / L; the inorganic phosphorus source is selected from at least one of disodium hydrogen phosphate, sodium dihydrogen phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate; in solution B, the molar concentration of the inorganic phosphorus source in terms of P is 0.5-1 mol / L; the calcium source is selected from at least one of calcium chloride and calcium nitrate.

5. The filling injection according to claim 1, characterized in that: In the preparation method of porous hydroxyapatite, the polymer pore former is selected from at least one of polyvinyl alcohol, hydroxypropyl methylcellulose, chitosan, polydextrose, polyethylene, polypropylene, and polycarbonate; the ratio of the polymer pore former to Ca in the calcium source is 20-30g:1mol.

6. The filling injection according to claim 5, characterized in that: The polymer pore-forming agent is a compound of low molecular weight polyvinyl alcohol and high molecular weight polyvinyl alcohol, the number average molecular weight of the low molecular weight polyvinyl alcohol is 5000-8000 g / mol, and the number average molecular weight of the high molecular weight polyvinyl alcohol is 20000-30000 g / mol.

7. The filling injection according to claim 6, characterized in that: The mass ratio of the low molecular weight polyvinyl alcohol to the high molecular weight polyvinyl alcohol is 4-7:

1.

8. The filling injection according to claim 1, characterized in that: In the preparation method of porous hydroxyapatite, washing is performed with water until the pH value of the supernatant is 7-7.5, and then washing with ethanol; the calcination is performed at 320-360° C. for 6-10 hours in an oxygen-containing atmosphere.

9. The injection for filling according to claim 1, characterized in that: The aqueous solution for injection is physiological saline or a phosphate buffer solution with a pH of 6.8-7.2; an osmotic pressure regulator is also added to the filling injection to adjust the osmotic pressure of the injection to 290-330 mOsmol / kg, and the osmotic pressure regulator includes at least one of glycerol, mannitol, and sorbitol.

10. The injection for filling according to claim 1, characterized in that: The growth factor is selected from at least one of fibroblast growth factor, epidermal growth factor and keratinocyte growth factor.

11. The injection for filling according to claim 10, characterized in that: The filling injection also includes one or more of analgesics, vitamins, antibacterial agents, and antioxidants; the analgesics include lidocaine; the vitamins include vitamin C, vitamin D, vitamins, vitamin B6, and vitamin B7; and the antibacterial agents include benzalkonium bromide.

12. The method for preparing the injection for filling according to any one of claims 1 to 11, characterized in that: The following steps are involved: The porous hydroxyapatite is mixed evenly with the growth factor and water for injection to achieve sufficient loading of the porous hydroxyapatite with the growth factor, and then sodium hyaluronate and cross-linked sodium hyaluronate are added, mixed evenly, and sterilized to obtain a filling injection containing porous hydroxyapatite and sodium hyaluronate.

Citation Information

Patent Citations

  • Hydroxyapatite-containing injection filling preparation and preparation method thereof

    CN110292655A

  • Oxidized graphene insulating heat-radiating coating and preparation method thereof

    CN105086688A

  • Crosslinked hyaluronic acid-smooth hydroxyapatite gel and preparation method thereof

    CN117323471A